A stable and active three-dimensional carbon based trimetallic electrocatalyst for efficient overall wastewater splitting. (1st September 2021) - Kumar, Aniket; Hong, Jaewoon; Yun, Yejin; Jung, Hyeonjung; Lee, Kug-Seung; Han, Jeong Woo; Song, Sun-Ju
Abstract: The depiction of nanocatalysts for water splitting, which can easily be workable in polluted water that could address the issues of freshwater and energy scarcity. The development of a stable and cost-effective catalytic system that involves alloying of precious and non-precious metals may be an efficient approach to achieve the above goal. Herein, we report a three-dimensional carbon-based tri-metallic system as a multifunctional electrocatalyst having superior catalytic activity towards water splitting and degradation of organic contaminants present in sewage. Catalytic activity towards the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is enhanced in analogous to other state-of-art catalysts. The density functional theory (DFT) strategies are applied to find the reason behind the superior activity of the designed catalyst toward wastewater electrocatalysis. Furthermore, this work provides a new approach towards the improvement of multifunctional electrocatalysts with broad potential for efficient and effective electrochemical energy storage and conversion. Graphical abstract: Highly active graphite (G)/Sn–Pt–Co nanocatalyst has been designed via simple impregnation route and used as an efficient trifunctional catalyst for HER/OER/Nitro compound reduction. Image 1 Highlights: The Sn–Pt–Co/G as a trifunctional nanocatalyst synthesized via simple impregnation route. The trimetallic nanocatalyst synergistically exhibit better performance in sewage water for water splitting. The designed electrocatalyst exhibits high activity with superior durability. This electrocatalyst system can be used to clean sewage and simultaneously produce hydrogen and oxygen.